Panentheism and the "Most Nonsensical Superstition" of Polytheism: A Critical Examination of K. C. F. Krause's Reception of Vedānta and Hindu Religion - Medhananda, Swami (European journal for philosophy of religion, 2022)
The German philosopher K. C. F. Krause (1781-1832) found deep conceptual parallels between his panentheistic system and the Indian philosophy of Vedānta. This article critically examines Krause's understanding of Vedānta and popular Hindu religion. I argue that while Krause was correct in viewing the mystical panentheistic doctrine of Vedānta as a precursor to his own philosophy, he was also frequently misled by unreliable translations and secondary texts. Krause, I suggest, was mistaken in characterizing the Hindu practice of image worship as "polytheism" and "idolatry," and I contend, from a Vedāntic standpoint, that Krause's denial of the divinity of Jesus is inconsistent with his own panentheistic metaphysics.